Compositional variances in petal cuticular wax of eight rose species and their impacts on vase life under water-loss stress - Hao, Xuan; Lv, Junheng; Zhao, Zixian; Tong, Yuxin; Deng, Minghua; Wen, Jinfen (Frontiers in Plant Science, 2024)
Cuticular wax is the first barrier between plants and the environment.Here, the densities of cuticular wax crystals on the petals of eight rose cultivars were determined to be sparse; the crystals were mostly granular and only a few rod-shaped crystals were observed in 'Sweet'. The total contents and chemical compositions of waxes were significantly different among the rose varieties. The waxes were mainly composed of n-alkanes, iso-alananes and alkenes. Under water-loss stress, 'Diana' and 'Carola' cultivars, having high petal wax contents, had low water permeability levels, long vase lives, high relative water contents and low relative conductivity levels.However, the low wax contents of the 'Jubilance' and 'Candy Avalanche' cultivars resulted in high water permeability levels and short vase lives. Pearson correlation analyses showed the total wax content in petal epidermis was positively correlated with vase life. The data provide novel insights into the compositional variances in the cuticular waxes of rose petals and their impacts on cut rose vase lives.